Peningkatan Produktifitas Pencampuran Bahan Cat Pada Skala Industri Rumah Tangga - Sidiq Ruswanto (Jurnal Sains dan Ilmu Terapan, 2019)
Presence of technology is very important to support small-scale industry. Mixer paint machine is efficient technology and useful for small-scale industry. It is very effective and efficient if it was compared with another mixer of paints machine, so it can help as an exact mixer of paint machine. It function tomix materials for making paint and use tangential force principle, work principleof propeller shaft as a mixer, solvent and destroyer thorough process of materials friction with tangential force that appear because circle that produced from electrical motor. Circle in mixer shaft made constant, it means to maximize product from paint solution in order to has homogenous. Therefore mixer of paint machine that became a paints that measure up as get homogenous are not faded If brushed or even if strikes water. So this machine is useful for small-scale industry.